PERAMALAN VOLATILITAS MENGGUNAKAN MODEL GENERALIZED AUTOREGRESSIVE CONDITIONAL HETEROSCEDASTICITY IN MEAN (GARCH-M) (Studi Kasus pada Return Harga Saham PT. Wijaya Karya) - Ratnasari, Dwi Hasti; Tarno, Tarno; Yasin, Hasbi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Stock return volatility in the markets of developing countries (emerging markets) is generally much higher than the markets of developed countries. High volatility illustrates the level of high risk faced by investors due to reflect fluctuations in stock price movement. Therefore, it is probable, stock investments that are carried in Indonesia have a high risk opportunity. Important properties are often owned by time series data in the financial sector in particular to return data that the probability distribution of returns is fat tails and volatility clustering or often referred to as a case of heteroscedasticity.Time series models that can be used to model this condition are ARCH and GARCH. One form of ARCH/GARCH is Generalized Autoregressive Conditional Heteroscedasticity In Mean (GARCH-M). The purpose of this study is to predict volatility by using GARCH-M model in the return data analysis of daily stock price closing of Wijaya Karya (Persero) Tbk from October 18, 2012 until March 14, 2014 by using the active days (Monday to Friday). The best model is used for forecasting the volatility case in the stock price return of PT. Wijaya Karya is ARIMA (0,0, [35]) GARCH (1,1)-M. Keywords: Stocks, Volatility, Generalized Autoregressive Conditional Heteroscedasticity in Mean (GARCH-M)